THE RISK FACTOR RELATED MALNUTRITION IN CHILDREN AGE 24 – 59 MONTH IN PUBLIC HEALTH CENTER CIMAHI SELATAN - Dyan Kunthi Nugrahaeni; Teguh Akbar Budiana; Gia Ulfah Deviyan (SEKOLAH TINGGI ILMU KESEHATAN (STIKes) INDRAMAYU, 2020)
The nutritional status of children under five years old has an impact on the physical, motor and intelligence development. Malnutrition causes multisystem disorders that result in imbalance of the body and stunted growth. This study aims to identify the risk factor of malnutrition based on family income, history of low birth weight, energy-protein intake at Puskesmas Cimahi Selatan. The research design used case control study. The sample of cases were children under five who have malnutrition based on the weight-for-age index as much as 38 childrens, while the control sample were children with not malnutrition. The sampling technique used purposive sampling. Measuring variables of family income, history of LBW through interviews, energy-protein intake used food recall 2x24 hour. Data were analyzed by univariate and bivariate with Chi-Square test. The variables related with malnutrition were family income (p-value= 0.001; OR= 2.39; 95%CI= 1.36-4.20), history of LBW (p-value= 0.003; OR= 2.17; 95%CI= 1.55-3.03) and energy intake (p = 0.004), variable protein intake was not significant (p-value= 1.0). The risk factors malnutrition are family income, history of low birth weight, and energy intake. Malnutrition can be prevented with monitoring growth and development and fulfilling the nutritional intake of children under five, especially energy.